2019
DOI: 10.1111/jwas.12591
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding a novel multistrain yeast fraction on European seabass (Dicentrachus labrax) intestinal health and growth performance

Abstract: Fish were fed a single‐strain yeast fraction (SsYF; 2 g/kg) or a multistrain yeast fraction (MsYF; 0.8 g/kg) for 10 weeks. The results demonstrated significant (p ≤ 0.03) elevations in weight gain, specific growth rate, protein efficiency ratio, and feed conversion ratio in fish fed the yeast fraction‐supplemented diets. In the distal intestine, a significant elevation in microvilli density was observed after 5 and 10 weeks of dietary supplementation with MsYF and SsYF, respectively, compared to control fed fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 56 publications
1
26
0
1
Order By: Relevance
“…RNA from DI sections was extracted using TRI reagent (Sigma-Aldrich, Poole, United Kingdom) according to the manufacturer’s instructions, with some modifications as described by Rawling et al (2019). To remove any contaminating genomic DNA, the RNA was treated with Dnase (TURBO DNA-free TM , Ambion) following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…RNA from DI sections was extracted using TRI reagent (Sigma-Aldrich, Poole, United Kingdom) according to the manufacturer’s instructions, with some modifications as described by Rawling et al (2019). To remove any contaminating genomic DNA, the RNA was treated with Dnase (TURBO DNA-free TM , Ambion) following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…2019; Rawling et al . 2019). The expression and incorporation of recombinant proteins into the cell wall of yeast, especially Saccharomyces cerevisiae , represents an outstanding tool for displaying and engineering of many proteins, and yeast surface display nowadays is a well‐established technology.…”
Section: Probiotics Surface Display Systemmentioning
confidence: 99%
“…The test diet was then produced by supplementing, prior to cold extrusion, the required amount of basal diet with the multi-strain yeast fraction product (MsYF, Lallemand SAS, Blagnac, France) at 1.5 g/kg of feed ( Table 1 ). The composition and structure of each yeast strain fraction present in the MsYF product was reported previously [ 24 ]. The diets were produced by mechanically stirring the ingredients into a homogenous mixture using a Hobart food mixer (Hobart Food Equipment, Australia, model no: HL1400— 10STDA mixer).…”
Section: Methodsmentioning
confidence: 99%
“…Initial investigations using human monocytes in vitro identified that exposure to the MsYF increased the production of the pro-inflammatory cytokine TNF-α and respiratory burst capacity. Furthermore, analysis of the glycoprotein structure showed a higher degree of longer unfolded glycoproteins presented by MsYF compared to a single strain yeast fraction, which could confer more sites for interaction with host innate immune cells [ 24 ]. Previously, our group reported that dietary supplementation with the MsYF at a dose below 1g /kg feed modulated the intestinal expression of specific genes markers of intestinal health and immunity, increased the intestinal surface area, i.e.…”
Section: Introductionmentioning
confidence: 99%